Gingival Angiosarcoma: A Case Report and Clinicopathologic Review of 32 Cases of Primary Gingival Angiosarcoma - Nusrath, Syed (Indian J Surg Oncol, 2020)
Angiosarcoma is a malignant neoplasm of mesenchymal origin arising from vascular endothelium and most commonly involves extremities. Gingival angiosarcoma is a rare sporadic occurring tumor. We report a case of primary angiosarcoma of gingiva along with a review of 31 cases of primary gingival angiosarcoma reported in literature till 2018. A 30-year-old lady presented with recurrent gingival swelling over central mandible. She had no palpable cervical lymphadenopathy. She underwent central marginal mandibulectomy. Final histological analysis with immunohistochemistry was suggestive of the angiosarcoma of the gingiva. She is 50 months postoperative and doing well.